Effective desensitization for a strong donor‐specific HLA antibody in a case of HLA‐mismatched allogeneic hematopoietic cell transplantation. (6th August 2019) - Misra, Maneesh K.; Xin, John J.; Brown, Nicholas K.; Weidner, Jerome G.; Upchurch, Rebecca L.; Bishop, Michael R.; Wool, Geoffrey D.; Artz, Andrew S.; Marino, Susana R.
Abstract : We describe a unique ABO compatible and 9/10 HLA‐matched case of successful allogeneic hematopoietic cell transplantation (HCT) after effective desensitization of a strong anti‐HLA‐A24 donor‐specific antibody (DSA) with mean fluorescence intensity of approximately 18 000. Due to absence of a suitable matched unrelated donor the patient sibling was considered the best available donor, and it was decided to desensitize patient prior to transplant. The strength of HLA‐A24 DSA slowly decreased over the course of treatment, necessitating a total of 23 sessions of therapeutic plasma exchange in order to bring the DSA strength to undetectable levels, followed by a successful transplant. In summary, the outcome of this case shows effective application of desensitization treatment to remove strong DSA in HCT patients.